Uncemented Reverse Total Shoulder Arthroplasty as Initial Treatment for Comminuted Proximal Humerus Fractures. Issue 7 (July 2019) - Wright, Jon O.; Ho, Anthony; Kalma, Jeremy; Koueiter, Denise; Esterle, Jason; Marcantonio, David; Wiater, J. Michael; Wiater, Brett
Abstract : Objectives: To determine whether uncemented implants would provide similar outcomes while avoiding the complications associated with cement in the treatment of elderly patients with proximal humerus fractures (PHFs) with primary reverse total shoulder arthroplasty (RTSA). Design: Case series. Setting: A single Level I trauma center. Patients/Participants: A prospectively obtained cohort of 30 patients who underwent uncemented RTSA as initial treatment for a comminuted PHF: 4 male, 26 female; average age 71 ± 11 years. Intervention: Uncemented RTSA. Main Outcome Measures: (1) Radiographic analysis, (2) postoperative clinical range of motion, and (3) functional outcome scores: the American Shoulder and Elbow Surgeons Shoulder score and the Simple Shoulder Test score. Results: Radiographic analysis showed 97% achieved stable humeral stem fixation and 70% had healing of the tuberosities in anatomical position. Average range of motion was 130 ± 31 degrees of forward flexion, 32 ± 18 degrees of external rotation, and internal rotation to the midlumbar spine. Average American Shoulder and Elbow Surgeons Shoulder score was 82.0 ± 13.5 (with an average pain rating of 0.8 ± 1.3), and average Simple Shoulder Test score was 69.4% ± 19.1%. Conclusions: Our data show that treatment of comminuted PHFs in elderly patients with uncemented RTSA can consistently produce good clinical outcomes with a low rate of complications and suggest that cement may not be necessary for RTSA in the trauma setting. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.